Perancangan Business Continuity Plan Sebuah Perusahaan Paku di Surabaya - Avelia Wijaya; Kriswanto Widiawan (Jurnal Titra, 2017)
PT. X is one of the industrial company engaged in the field of construction materials, especially nails and iron materials with products such as wire nails, nail, bendrad, iron pieces, tacks, self drilling screw, drywall screw and low, medium and high carbon . Condition of PT. X does not have a Business Continuity Plan (BCP), where the BCP is a process of making a plan to identify and assess the risks that can occur to an organization that can anticipate the termination of business activities. BCP can help PT. X to keep running its business processes under any circumstances so as to prevent the occurrence of termination of business processes. The purpose of this design is designing the BCP document in accordance with the conditions of the company today with no restriction does financial analysis, design Contingency Plan (CP) and the results are more focused on the design of disaster-related incidents / accidents that may occur. BCP design process at PT. X is divided into four stages. The first stage is to collect data in the form of a list of interview questions, collect the necessary corporate documents and seek guidance in designing the BCP in the form of ISO 22301: 2012. The second stage is to process data in the form of interviews and company documents that have been collected as the basis of BCP design and guidance of ISO 22301: 2012 to determine what documents need to be arranged in BCP design. The third stage is compiling BCP team, Emergency Response Document, Crisis Management and Communication Document, Business Recovery Document and Overview Document. The BCP team was formed to determine the responsibilities and authorities in carrying out the BCP design and to plan the actions that need to be taken in the face of the incident. Emergency Responsedocument is used to determine management measures and anticipation when the incident occurred. Crisis Management and Communication document is used to determine further treatment after the incident occurred. Documents Business Recovery is used to determine who carried out during the recovery process. Overview document used to facilitate the passage of the BCP in the form of an introduction, purpose, commitment and responsibility and authority to run the BCP.